Ebu’l-Abbas es-Serûcî’nin Nefehâtu’n-nesemât fî Vusûli İhdâi’s-sevâbi li’l-emvât İsimli Risalesi Tahric, Tahlil ve Tercüme / The Article of Abu’l-Abbas as-Seruci Nefehatu’n-nesemat fî Vusuli İhdai's-sevabi li'l-emvat -Determining the Sources of Hadith Analysis and Translation - Habergetiren, Ömer Faruk; Koçyiğit, Yakup (Journal of History Culture and Art Research, 2018)
Abstract Ebu’l-Abbâs es-Serûcî is a Faqih that has worked as the Kâdi’l-kudât (Head Jurist) in the capitol of Egypt, Cairo, for long years. During his years of work, he kept his connection with teaching and learning and wrote many books. He became famous for his commentary(sharh) el-Gâye that he wrote on Merginânî’s el-Hidâye. which is considered to be one of the central sources in the Hanafi madhab. Among the authors many books in many different fields are also risalahs (small books) that he wrote to answer certain questions directed to him. One of these risalahs is Nefehâtu’n-nesemât. The author speaks on the topic of reading Qur’an for those who passed away and bestowing the reward to them. He tries to prove the permissibility of this practice, which, to this day, is still argued among the Fuqaha. In his work the author includes verses of Qur’an and hadiths that form the basis for this issue regarding fiqh. He also includes sayings of other people and dreams that cannot be seen as evidence. The author’s claim that there is ijma (unanimity) regarding this issue can be understood to mean that the Muslim community broadly accepts this practice. The hadiths that are given as evidence are mostly from sahih(reliable) sources but there are also those who are deemed daʻīf (weak) or mawdu’ (fictitious). The dreams in general and the saying of those who are not among the Fuqaha can be seen as an intention to support the matter. From the verses of Qur’an and the hadith in the text we can understand that this practice was considered within the concept of dua(prayer) and was performed in every community since the Sahabah (the companions of the Prophet-p.b.u.h-) and became a tradition and that we should not reject it altogether. In this work the risalah was analysed, the hadiths that are used are evaluated and their sources are determined. The original Arabic text and the translation are also given in the appendix. Öz Ebu’l-Abbâs es-Serûcî uzun yıllar Mısır ve Kahire’de Kâdi’l-kudâtlık (Baş kâdılık) görevinde bulunmuş bir fakihtir. Görev yaptığı sürede eğitim-öğretim hayatından kopmamış, pek çok eser telif etmiştir. Hanefi mezhebinin temel kaynakları arasında yer alan Merginânî’nin el-Hidâye kitabı üzerine yapmış olduğu el-Gâye isimli şerhiyle meşhur olmuştur. Farklı konularda telif etmiş olduğu eserleri arasında kendisine sorulan sorulara cevap vermek amacıyla yazmış olduğu küçük risaleler de bulunmaktadır. Bunlardan birisi de Nefehâtu’n-nesemât adlı risaledir. Yazar, risalede vefat eden kimseler için Kur’an okuma ve sevabını onlara bağışlama konusunu ele almaktadır. Günümüzde de İslam hukukçuları arasında tartışmalı olan bu konunun caiz oluşunu ispat etmeye çalışmaktadır. Eserde konunun dini-hukuki alt yapısını oluşturan ayet ve hadislere yer verilmiş ayrıca bir delil olarak nitelendirilemeyecek kişilere ait söz ve rüyalar da nakletmiştir. Yazarın bu konuda görüş birliği (icma) bulunduğu iddiası, Müslümanlar arasında genel bir kabulün bulunduğu şeklinde yorumlanabilir. Delil olarak gösterilen hadisler genelde sahih olarak kabul edilen kaynaklarda yer almaktadır. Bunlar arasında hadis otoritelerince zayıf ve mevzu olarak nitelenenler de bulunmaktadır. Rüya ve hukukçu olmayan kimselerden nakledilen sözler ise konuyu destekleme tarzında düşünülebilir. Metinde yer verilen ayet ve hadislerle bu konunun dua kapsamında değerlendirildiği, sahabe döneminden beri her toplumda uygulanarak örf haline gelen bu davranışın tamamen ret edilmemesi gerektiği sonucu ortaya çıkmaktadır. Bu çalışmada eser tahlil edilerek, kaynak olarak kullanılan hadislerin tahriç ve değerlendirilmesi yapılmış, Arapça metni ve tercümesi de ek olarak verilmiştir.